Applied ethics in the fractured state - Grant, Bligh; Drew, Joseph S. (Political scientist); Christensen, Helen E. (Emerald Publishing Limited, 2018)
This book brings together the refereed proceedings of the 24th Annual Conference of the Australian Association of Professional and Applied Ethics (AAPAE) 'Applied Ethics in the Fractured State', held at the Institute for Public Policy and Governance, University of Technology Sydney in June 2017. The book is eclectic, with chapters on health regulation in Australia, Eastern ethical theorising (Confucianism; Buddhism), euthanasia and community engagement, all of which are examined from the unique perspective that Research in Ethical Issues in Organizations affords its contributors.
Prelims -- Introduction: Applied ethics in the fractured state -- Ethics, Roles, and Confucianism -- The Unique Perspective on Intention (Cetanā), Ethics, Agency, and the Self in Buddhism -- Rawls, Reasonableness, and Conscientious Objection in Health Care -- The Other Side of Euthanasia: A Practice Perspective from Australia -- Natural Law, Non-Voluntary Euthanasia, and Public Policy -- When Health Workforce Governance Met Regulatory Capitalism: Australia's National Arrangements for Health Professional Registration and Accreditation -- Impact of the National Mutual Acceptance on Research Governance Practices in Victorian Public Healthcare Agencies -- Community Engagement and Professionalization: Emerging Tensions -- Index.
Includes index.
Print version record
Keywords: Applied ethics -- Congresses; Business & Economics -- General; Business & management